Implikasi Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja terhadap Perlindungan Pekerja Outsourcing di Indonesia (Jurnal De Jure Muhammadiyah Cirebon, 2025)
The implementation of outsourcing in Indonesia has become a highly popular and widespread practice. The regulations regarding outsourcing are governed by Law Number 13 of 2003 concerning Manpower, which was later amended by Law Number 11 of 2020 concerning Job Creation. These regulatory changes have had a significant impact on the provisions related to outsourcing workers, particularly in terms of fulfilling workers' rights and improving their welfare. This study uses a normative legal method with a legislative approach. The findings of this study indicate that, although the government has made efforts to provide legal protection for outsourcing workers through the Job Creation Law, its implementation is still not optimal. One of the causes is the weak supervision of the enforcement of workers' rights and the limited access workers have to obtain protection for their rights.Keywords: Outsourcing, Job Creation Law, Fulfillment of Workers' Rights